Hakikah Manusia Sebagai Makhluk Pedagogik dalam Perspektif AlQuran - Muhamad Parhan; Nurti Budiyanti; Auliya Fitria (LPPM IAIN Sorong, 2021)
Allah SWT gave knowledge to Prophet Adam AS as well as all of us who are descendants of the children of Adam. There is a difference between Prophet Adam AS in obtaining knowledge directly from Allah SWT, while we are not taught directly by Allah SWT but given the potential by Allah to explore knowledge such as through the Qur'an and education. Al-Qur'an is the word of God which is used as a guide for life for Muslims who have no doubt in it. While education is an effort made by humans with various devices, characters and existence. In the Qur'an there are various signs related to educational issues that are very important, if the Qur'an is studied in depth, we will get related to the basic principles of education, which we can then use as inspiration in developing quality education.